Formulasi Model Perencanaan Penjualan Produk PD.Tataka Sumber Sentosa Berdasarkan Metode Peramalan - Yoga Esa Ardhana; Sutresna Juhara; Muhammad Yus Firdaus (Universitas Islam Syekh Yusuf Tangerang, 2023)
This study aims to formulate a product sales planning model at Pd. Tataka Sumber Sentosa uses the right forecasting method. Forecasting method is the key in confirming. In this study an analysis of the products was carried out, namely buis concrete and u-ditch. Data analysis is used as a basis for analyzing using forecasting methods such as the Moving Average, Exponential Smoothing, and Linear Trend Line Models of product sales planning formulation results. It can be concluded from the three forecasting models that the best is forecasting a 40 cm concrete bus with the Linear Trend Line Model results the error value of the 40 cm concrete buis with the Linear Trend Line Model is the value of MAD = 1.19, MSE = 2.048, MAPE = 2.412, and it can be concluded that the next forecast = 52 then the forecasting model chosen to determine forecasts for the next 6 months using the Linear Trend Line Model. Because the results of the analysis show that historical sales data and analyzing market demand trends are important steps in selecting the appropriate forecasting model.